Bureaucratic Features of the Administrative Reforms in Chile in the 1880s - Barria-Traverso, D (UNIV LOS ANDES, FAC CIENCIAS SOC, 2015)
In the 1880s, Chile experienced important changes in different social spheres that questioned the operating efficiency of state institutions. In order to cope with these difficulties, a broad process of administrative reform was initiated, especially with respect to the adoption of bureaucracy as the way to design public administration. In this regard, the article analyzes the organizational design of a series of institutions so as to evaluate how the characteristics of said system were adopted in Chilean public administration. Based on the study of different documents, it concludes that a series of bureaucratic characteristics functional division, formal rules and specialization were adopted for the purpose of overcoming the operational difficulties experienced throughout the decade.